Immunogenicity and Protective Efficacy of T-Cell Epitopes Derived From Potential Th1 Stimulatory Proteins of Leishmania (Leishmania) donovani - Joshi, Sumit; Yadav, Narendra Kumar; Rawat, Keerti; Kumar, Vikash; Ali, Rafat; Sahasrabuddhe, Amogh Anant; Siddiqi, Mohammad Imran; Haq, Wahajul; Sundar, Shyam; Dube, Anuradha (Frontiers in Immunology, 2019)
Development of a suitable vaccine against visceral leishmaniasis (VL), a fatal parasitic disease, is considered to be vital for maintaining the success of kala-azar control programs. The fact that Leishmania-infected individuals generate life-long immunity offers a viable proposition in this direction. Our prior studies demonstrated that T-helper1 (Th1) type of cellular response was generated by six potential recombinant proteins viz. elongation factor-2 (elF-2), enolase, aldolase, triose phosphate isomerase (TPI), protein disulfide isomerase (PDI) and p45, derived from a soluble antigenic fraction (89.9–97.1 kDa) of Leishmania (Leishmania) donovani promastigote, in treated Leishmania patients and golden hamsters and showed significant prophylactic potential against experimental VL. Moreover, since, it is well-known that our immune system, in general, triggers production of specific protective immunity in response to a small number of amino acids (peptide), this led to the identification of antigenic epitopes of the above-stated proteins utilizing immunoinformatics. Out of thirty-six, three peptides-P-10 (enolase), P-14, and P-15 (TPI) elicited common significant lymphoproliferative as well as Th1-biased cytokine responses both in golden hamsters and human subjects. Further, immunization with these peptides plus BCG offered 75% prophylactic efficacy with boosted cellular immune response in golden hamsters against Leishmania challenge which is indicative of their candidature as potential vaccine candidates.